Monitoring air quality index with EWMA and individual charts using XGBoost and SVR residuals - Zulfani Alfasanah; M. Zaim Husnun Niam; Sri Wardiani; Muhammad Ahsan; Muhammad Hisyam Lee (MethodsX)
PM2.5 air pollution poses significant health risks, particularly in urban areas such as Jakarta, where concentrations frequently surpass acceptable levels due to rapid urbanization. This study addresses autocorrelation in air quality data and evaluates the monitoring performance of XGBoost and Support Vector Regression (SVR) models using Individual and Exponentially Weighted Moving Average (EWMA) Charts. PM2.5 levels were obtained from Jakarta's Air Quality Index. The findings reveal that the SVR model effectively manages autocorrelation, while the combination of XGBoost and the EWMA chart yielded superior monitoring performance. Specifically, this approach detected only one out-of-control (OOC) point in Phase II and none in Phase I, with identified shifts ranging from moderate to large. Overall, the XGBoost and EWMA chart integration offers a robust solution for precise air quality monitoring and minimizes false alarms. The identification of OOC points provides actionable insights by highlighting significant deviations in air quality data that may require immediate intervention.Key points: • SVR and XGBoost model regression was introduced to enhance forecasting accuracy. • EWMA chart based on XGBoost residuals has better monitoring results.